2011
DOI: 10.1007/s10637-011-9687-4
|View full text |Cite|
|
Sign up to set email alerts
|

A phase II open-label randomized study to assess the efficacy and safety of selumetinib (AZD6244 [ARRY-142886]) versus capecitabine in patients with advanced or metastatic pancreatic cancer who have failed first-line gemcitabine therapy

Abstract: Selumetinib is a potent, selective MEK inhibitor with efficacy in several tumor models. This study compared selumetinib with capecitabine in patients with advanced or metastatic pancreatic cancer who had been pretreated with a gemcitabine-based regimen. In this randomized, multicenter phase II study (NCT00372944), patients received either 100 mg oral selumetinib twice daily or 1,250 mg/m(2) oral capecitabine twice daily for 2 weeks followed by a 1-week break, given in 3-weekly cycles. The primary endpoint was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(122 citation statements)
references
References 33 publications
(32 reference statements)
4
115
1
2
Order By: Relevance
“…However, two phase II studies of MEK inhibitors have failed to demonstrate any significant survival advantage for patients with pancreatic cancer (38,39). Furthermore, although MEK inhibition conferred a significant survival advantage in the present orthotopic pancreatic cancer xenograft model, the effect was somewhat limited (median survival of 82 days vs. 101 days for vehicle vs. PD325901, respectively).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, two phase II studies of MEK inhibitors have failed to demonstrate any significant survival advantage for patients with pancreatic cancer (38,39). Furthermore, although MEK inhibition conferred a significant survival advantage in the present orthotopic pancreatic cancer xenograft model, the effect was somewhat limited (median survival of 82 days vs. 101 days for vehicle vs. PD325901, respectively).…”
Section: Discussionmentioning
confidence: 57%
“…One plausible explanation for these limitations may be that oncogenic pathway(s) other than RAS-MEK-ERK may also contribute to progression of early invasive cancers to aggressive malignant cancers, such as locally disseminated or distant metastatic cancers. Indeed, the two previous phase II studies of MEK inhibitors enrolled patients with metastatic or refractory pancreatic cancers (38,39). Furthermore, PANC-1 cells, from which we developed our orthotopic models, were derived from locally disseminated pancreatic cancers (40).…”
Section: Discussionmentioning
confidence: 99%
“…AZD6244 is a potent, selective, and orally available MEK1/2 inhibitor. Previous studies have shown that the inhibition of MEK1/2 can induce apoptosis by inhibiting ERK-mediated B-cell lymphoma 2 phosphorylation and stabilization (16,17). Currently available MEK1/2 inhibitors have shown moderate single-agent activity in various tumors (18).…”
Section: Discussionmentioning
confidence: 99%
“…Selumetinib, a mitogen-activated protein kinase inhibitor, demonstrated similar efficacy as capecitabine in a phase II study (84), and was further tested in combination with erlotinib in the second line setting (85). There were no responders but median OS was about 7.5 months with 51% disease control rate.…”
Section: Kras and Associated Targetsmentioning
confidence: 99%